2022
DOI: 10.7759/cureus.24689
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Prolonged Water-Only Fasting Followed by a Whole-Plant-Food Diet on Salty and Sweet Taste Sensitivity and Perceived Intensity, Food Liking, and Dietary Intake

Abstract: The overconsumption of calorie-dense foods high in added salt, sugar, and fat is a major contributor to current rates of obesity, and methods to reduce consumption are needed. Prolonged water-only fasting followed by an exclusively whole-plant-food diet free of added salt, oil, and sugar may reduce the consumption of these hyper-palatable foods, but such effects have not been quantified. Therefore, we conducted a preliminary study to estimate the effects of this intervention on salty and sweet taste detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A main criticism of restrictive diets is their lack of long-term adherence [ 4 ], but we found that six weeks after returning home, there was an improvement in dietary adherence. This may be due to the potential effects of fasting on taste adaptation, particularly on salty and sweet food sensitivity, which may reduce the need for added salt, oil, or sugar, and allow for better adherence [ 36 ]. There are still unanswered questions about how an SOS-Free Diet impacts short- and long-term health outcomes, and whether individual dietary changes such as the addition of leafy green vegetables versus the elimination of added salt, oil, or sugar, impact health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A main criticism of restrictive diets is their lack of long-term adherence [ 4 ], but we found that six weeks after returning home, there was an improvement in dietary adherence. This may be due to the potential effects of fasting on taste adaptation, particularly on salty and sweet food sensitivity, which may reduce the need for added salt, oil, or sugar, and allow for better adherence [ 36 ]. There are still unanswered questions about how an SOS-Free Diet impacts short- and long-term health outcomes, and whether individual dietary changes such as the addition of leafy green vegetables versus the elimination of added salt, oil, or sugar, impact health.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely reported that humans have practiced therapeutic water-only fasting for more than two thousand years and there is more than a century of published literature on the physiological and clinical effects of water-only fasting in humans. Over the past decade, clinical research into the beneficial and adverse health effects of water-only fasting has progressed with a level of scientific rigor not previously reported [ 6 , 7 , 8 , 9 , 10 , 26 , 36 ]. Nonetheless, there is still a concern about the safety and practicality of prolonged water-only fasting in humans [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants stayed onsite at a residential fasting center in order to receive medical supervision while prefeeding, fasting, and refeeding for a median (range) of 2 (1-4), 11 (7-40), and 5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) days, respectively (ST3). Participants were instructed to continue eating an SOS-free diet while offsite between EOR and 6wFU visits and did not receive further dietary instruction thereafter.…”
Section: Treatment and Visit Characteristicsmentioning
confidence: 99%
“…[9; 10; 11] Preliminary research suggests that medically supervised, prolonged water-only fasting followed by an exclusively whole-plant-food diet free of added salt, oil, and sugar (SOS-Free Diet) has a very low risk of causing a severe or serious adverse event, results in immediate and sustained improvements in blood pressure and other biomarkers of CVD risk, and may improve adherence to diet and lifestyle modifications. [12; 13; 14; 15; 16] In order to continue evaluating if the intervention has potential as a HTN treatment, we conducted a single-arm pre-post interventional trial with the primary aim of assessing safety and feasibility in people with stage 1 and 2 hypertension by systematically collecting and reporting adverse events and treatment deviations as well as study retention rate, ability to complete minimal fast length, and self-reported intervention acceptability. Additionally, we measured the immediate, sustained, and long-term effects of the full intervention on BP and other cardiometabolic risk factors.…”
Section: Introductionmentioning
confidence: 99%